Friday
March 24, 2017

Post a New Question

Posted by on Tuesday, May 13, 2014 at 10:53am.

y-1/x+3=-3/4 solving for y. Please show steps so that I can get a better understanding of this.

  • Algebra - , Tuesday, May 13, 2014 at 11:35am

    y-1/x+3=-3/4

    y-1/x+ 1/x + 3-3 = -3/4 + 1/x -3
    y - 0 + 0 = -3/4 - 3 + 1/x
    y = (-3 - 12)/4 + 1/x
    y = -15/4 + 1/x

  • Algebra - , Tuesday, May 13, 2014 at 12:45pm

    Assuming the usual carelessness with parentheses, I see it as follows:

    (y-1)/(x+3) = -3/4
    y-1 = -3/4 (x+3)
    y = -3/4 (x+3) + 1
    y = -3/4 x - 5/4
    y = -(3x+5)/4

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question